LUBRICANT OIL CONSUMPTION IN RORAIMA’S AGRIBUSINESS: A LOCAL DISTRIBUTOR’S PERSPECTIVE - da Silva, Edgley Soares; Barros Júnior, José Américo; Barros, Manoel Felipe Brandão; Gonçalves, Anderson Carlos de Melo; Reyes, Veronica Nathaly Arevalo; Monteiro Neto, João Luiz Lopes; Cruz, Ana Bárbara de Souza (Seven Editora, 2026)
Agribusiness is one of the main sectors economic of Roraima. Its growth, like that of other producing regions, is heavily reliant on the use of modern machinery and implements; however, the efficient use of these depends, among other factors, on the use of lubricating oils. Given this aimed to diagnose the consumption of lubricating oil in Roraima’s agribusiness sector based on sales from a local distributor, CR Distribuidora. The study was conducted from August to October 2025, using as data source the annual sales report provided by CR Distribuidora, covering the period from January 1, 2025 to August 31, 2025. The data were compiled, organized into spreadsheets, and subsequently graphs were created, in which the results were plotted as numerical values and percentages. Engine oil with a viscosity of 15W40 stood out as the most widely used. The municipality of Boa Vista showed the highest consumption volume, and preventive maintenance accounts for the largest share of consumption. Among the brands analyzed, Ipiranga was the most sought after, with the Brutus Performance 15W40 product being particularly noteworthy, while in the Texaco line, the Ursa Premium TDX 15W40 was the most representative. It is concluded that the consumption of lubricating oils in the state of Roraima is strongly associated with the performance and maintenance of agricultural machinery and implements, especially in the use of engine oil during preventive maintenance of large tractors.